Finite element micromechanics model of impact compression of closed-cell polymer foams - Mills, N.J.; Stämpfli, R.; Marone, F.; Brühwiler, P.A. (International journal of solids and structures, 2009)
Finite element analysis, of regular Kelvin foam models with all the material in uniform-thickness faces, was used to predict the compressive impact response of low-density closed-cell polyethylene and polystyrene foams. Cell air compression was analysed, treating cells as surface-based fluid cavities. For a typical 1 mm cell size and 50 s −1 impact strain rate, the elastic buckling of cell faces, and pop-in shape inversion of some buckled square faces, caused a non-linear stress strain response before yield. Pairs of plastic hinges formed across hexagonal faces, then yield occurred when trios of faces concertinaed. The predicted compressive yield stresses were close to experimental data, for a range of foam densities. Air compression was the hardening mechanism for engineering strains <0.6, with face-to-face contact also contributing for strains >0.7. Predictions of lateral expansion and residual strains after impact were reasonable. There were no significant changes in the predicted behavior at a compressive strain rate of 500 s −1.